TGF-β regulates Sca-1 expression and plasticity of pre-neoplastic mammary epithelial stem cells - Remšík, Ján; Pícková, Markéta; Vacek, Ondřej; Fedr, Radek; Binó, Lucia; Hampl, Aleš; Souček, Karel (Scientific reports, 2020)
The epithelial-mesenchymal plasticity, in tight association with stemness, contributes to the mammary gland homeostasis, evolution of early neoplastic lesions and cancer dissemination. Focused on cell surfaceome, we used mouse models of pre-neoplastic mammary epithelial and cancer stem cells to reveal the connection between cell surface markers and distinct cell phenotypes. We mechanistically dissected the TGF-β family-driven regulation of Sca-1, one of the most commonly used adult stem cell markers. We further provided evidence that TGF-β disrupts the lineage commitment and promotes the accumulation of tumor-initiating cells in pre-neoplastic cells.
Keywords: Gene Expression Regulation, Neoplastic; myši; Mammary Glands, Animal; Signal Transduction; Cell Plasticity; Cell Line, Tumor; Female; nádory prsu; Humans; plasticita buňky; ataxin-1; experimentální nádory mléčných žláz; rekombinantní proteiny; epitelo-mezenchymální tranzice; nádorové kmenové buňky; mléčné žlázy zvířat; lidé; Neoplastic Stem Cells; ženské pohlaví; Transforming Growth Factor beta; Epithelial Cells; Epithelial-Mesenchymal Transition; signální transdukce; Breast Neoplasms; Animals; epitelové buňky; transformující růstový faktor beta; zvířata; Mammary Neoplasms, Experimental; Mice; Receptor, ErbB-2; nádorové buněčné linie; receptor erbB-2; Ataxin-1; Recombinant Proteins; regulace genové exprese u nádorů